Solution heat treatment of plasma nitrided 15-5PH stainless steel - Part I: Improvement of the corrosion resistance - Borges, P. C.; Rocha, Luís Augusto Sousa Marques da [UNESP] (My University, 2011)
The results of the investigation on Solution Heat Treatment of Plasma Nitrided (SHTPN) precipitation-hardened steel 15-5PH are presented. The layers have been obtained by the plasma nitriding process followed by solution heat treatment at different temperatures. The influence of the solution heat treatment after nitriding on the dissolution process of the nitrided layer has been considered. The nitrided layers were studied by scanning electron microscopy, X-ray microanalysis (EDX), and X-Ray diffraction. Micro-hardness tests of the nitrided layers and solubilized nitrided layers have been carried out and interpreted by considering the processing conditions. It was found that high nitrogen austenitic cases could be obtained after SHTPN of martensitic precipitation-hardened steel (15-5PH). When Solution Heat Treatment (SHT) was performed at 1100 °C, some precipitates were observed. The amount of precipitates significantly reduced when the temperature increased. The EDX microanalysis indicated that the precipitate may be chromium niobium nitride. When the precipitation on the austenite phase occurred in small amount, the corrosion resistance increased in SHTPN specimens and the pit nucleation potential also increased. The best corrosion result occurred for SHT at 1200 °C.
Keywords: Solution heat treatment; Plasma nitriding; Precipitation-hardening stainless steel; 15-5PH; SHTPN; Corrosion resistance